Drought and soil nutrients effects on symbiotic nitrogen fixation in seedlings from eight Neotropical legume species. (20th January 2021) - McCulloch, Lindsay A.; Piotto, Daniel; Porder, Stephen
Abstract: Symbiotic nitrogen fixation is a dominant source of nitrogen to many terrestrial ecosystems and thus may influence their responses to global change. High legume species diversity and abundance are thought to lead to high rates of symbiotic nitrogen fixation in Neotropical forests. However, how changes in water and nutrient availability will affect symbiotic nitrogen fixation has only recently been explored, even as droughts begin to increase in severity and frequency in the Neotropics. To explore these effects, we grew eight species of Neotropical woody legume seedlings in a shadehouse for four months while manipulating soil water, phosphorus, and molybdenum availability. Overall, drought reduced nodule biomass, nitrogenase activity (acetylene reduction g ‐1 nodule), and acetylene reduction per seedling by 33%, 27%, and 41%, respectively, but reduced seedling biomass by only 18%. Species varied in the manifestation of drought effects. For example, drought reduced the probability that nodules formed in some species, but in others reduced the nitrogenase activity or acetylene reduction per seedling. In contrast, the effects of phosphorus and molybdenum availability were more species‐specific. However, fertilization did affect (both positively and negatively) one or more symbiotic nitrogen fixation response variables in two of the eight species. Our results indicate drought reduces symbiotic nitrogen fixation in Neotropical legume seedlings, but the mechanism of response may be species‐specific. Therefore, predicting the response of symbiotic nitrogen fixation in the Neotropics to a changing climate, with expected increases in drought frequency and severity, may require grappling with the diversity of responses among nitrogen‐fixing legumes. Abstract in Portuguese is available with online material Abstract : We grew eight species of Neotropical woody legume seedlings in a shadehouse for four months while manipulating soil water, phosphorus, and molybdenum availability. Drought reduced symbiotic nitrogen fixation by 27‐41% and only reduced seedling biomass by 18%, but this reduction in symbiotic nitrogen fixation to drought may be species‐specific. Therefore, predicting the response of symbiotic nitrogen fixation in the Neotropics to a changing climate, with expected increases in drought frequency and severity, may require grappling with the diversity of responses among nitrogen‐fixing legumes. Resumen: A fixação simbiótica de nitrogênio é uma das principais fontes de nitrogênio para muitos ecossistemas terrestres e, portanto, pode influenciar nas respostas desses ecossistemas às mudanças climáticas globais. Acredita‐se que a alta diversidade e abundância de espécies de leguminosas levem a altas taxas de fixação simbiótica de nitrogênio nas florestas neotropicais. No entanto, só recentemente tem sido investigado como as mudanças na disponibilidade de água e nutrientes afetam a fixação simbiótica de nitrogênio, mesmo com as secas começando a aumentar em severidade e frequência na região neotropical. Para explorar esses efeitos, cultivamos oito espécies de leguminosas lenhosas neotropicais em uma casa de vegetação por quatro meses, manipulando experimentalmente a disponibilidade de água, fósforo e molibdênio no solo. No geral, a seca reduziu a biomassa do nódulo, a atividade da nitrogenase (redução do acetileno em g ‐1 por nódulo) e a redução do acetileno por muda em 33%, 27% e 41%, respectivamente, porém a biomassa da muda reduziu em apenas 18%. As espécies variaram na resposta aos efeitos da seca. Por exemplo, a seca reduziu a probabilidade de formação de nódulos em algumas espécies, mas em outras reduziu a atividade da nitrogenase ou redução do acetileno por muda. Já os efeitos da disponibilidade de fósforo e molibdênio foram mais específicos à espécie. No entanto, a fertilização afetou (positiva e negativamente) uma ou mais variáveis de resposta à fixação simbiótica de nitrogênio em duas das oito espécies. Nossos resultados indicam que a seca reduz a fixação simbiótica de nitrogênio em mudas de leguminosas neotropicais, mas o mecanismo de resposta pode ser específico da espécie. Portanto, prever a resposta da fixação simbiótica de nitrogênio na região neotropical sob um clima em mudança, com aumentos esperados na frequência e severidade das secas, depende de um melhor entendimento da diversidade de respostas entre as espécies leguminosas fixadoras de nitrogênio.